Social science and socialising: adopting causal layered analysis to reveal multi-stakeholder perceptions of natural resource management in Australia - Green, M.; Dzidic, Peta (Routledge, 2014)
The social context of Natural Resource Management (NRM) in Australia is now considered to be a major contributing factor behind the success or failure of landscape improvement programmes. This paper investigates NRM social issues via an alternative interpretative method, Causal Layered Analysis (CLA). CLA was utilised in nine focus groups, comprising landholders and staff from NRM regional bodies in central west New South Wales. A multitude of stakeholder concerns emerged, particularly regarding the concept of sustainability and confusion over roles and responsibilities. We propose that continued use of CLA by those in the local catchment community can help overcome complexity in the social landscape and lead to more engaged and empowered communities.